Primera cita de nidificación del Jote de Cabeza Negra (Coragyps atratus) para Buenos Aires - Belenguer, Carolina (1997)
Wereporta nest of Black Vultures,the first for Buenos Aires Province.It was found on the ground in a coastal sand dune,covered by the endemic bush Neosparton darwinii.